Travel Management In Meeting Tourist Satisfaction Kota Lama Semarang - Desika Nur Jannah; Herman Novry Paninggiran; Almas Nabili Imanina (At-Tadbir : jurnal ilmiah manajemen, 2023)
This study aims to fulfill tourist satisfaction through quality travel management. This research is a qualitative research. The location of this research is in the Old City of Semarang. While the informants in this study were tourists from the Old City of Semarang. Based on the results of the discussion that has been presented, it is known that travel services in the Old City of Semarang are quite helpful for tourists. The travel management used is structured and directed, such as notification of information on every tourist spot visited and good communication with tourists. Good service providers can increase tourist satisfaction, build a good reputation, and drive the growth of the tourism industry as a whole. The focus of this research is the way the travel tour in serving the tourists who are being combined. Keywords: Management of Travel, Tourist Satisfaction, Tourist, Literature Review, Old City